Effects of abundance, water temperature and light on the turbulence and mixing generated by fish schools of different sizes in quiescent water in a laboratory - Ahani, Sana; Khorsandi, Babak (Frontiers in Marine Science, 2022)
The turbulence and mixing generated by schools of three fish species, namely koi, pangasius, and goldfish, were quantified in a series of controlled laboratory experiments. The effects of fish abundance, light, and water temperature on the turbulence parameters of the flow produced by the three fish species in a quiescent background were investigated by measuring the velocity field using acoustic Doppler velocimetry. It was observed that the turbulent flow was approximately homogeneous and isotropic and had low-mean velocities. The results show that increasing fish abundance and body size, dimming the ambient light, and increasing the water temperature increase the root-mean-square velocity, the integral time scale, and the rate of dissipation of turbulent kinetic energy. Consequently, fish abundance and body size, as well as environmental parameters, can influence fish-generated turbulence. To further quantify turbulent mixing, the dissipation rate, the mixing efficiency, and the vertical eddy diffusivity were extrapolated for the three fish species at their natural abundances. The dissipation rate of O(10-7-10-6) W/kg, the mixing efficiency of O(10-2-10-1), and the vertical eddy diffusivity of O(10-4) m2/s were estimated. These values are within the range of those of the physical sources. This demonstrates that the contribution of aquatic animals to the turbulent mixing of water environments may be significant. Furthermore, the dissipation rate and eddy diffusivity are found to increase with the Reynolds numbers of aquatic species.